Leveraging Waste Banks for Green Environment Sustainability: A Case Study of Community Collaboration in the Gemuruh District, Bandung City, Indonesia - Ester Manik; Ashila Dwiyanisa; Galih Putra Prawiranegara; Adinda Nuraini; Riska Yuni Astuti; Iasya Mardhiyyah; Octaviane Herawati (Majalah Bisnis & IPTEK, 2024)
Waste management is a critical issue worldwide, including in Indonesia. In recent years, there has been a growing focus on waste management due to population growth and rapid urbanization. This initiative emphasizes the implementation of technology and innovation in waste management and its impact on communities. The results show that the use of organic waste shredding machines, waste banks, and compost bags has improved waste management efficiency. Training on sorting inorganic and organic waste, as well as using shredding machines, has enhanced the knowledge and skills of the community. Pre-tests and post-tests indicate an increase in understanding and skills in waste management, highlighting the effectiveness of the training program. The community has positively responded to the implementation of technology and innovation. This initiative demonstrates that empowering creative economy through plastic waste recycling can have a positive impact on communities, particularly in raising awareness and skills in waste management.